PATTERNS OF FLOW OF TOMATO AND YAM AND THEIR CONTRIBUTIONS TO THE ECONOMIC GROWTH BENUE STATE - Dr.H.DOlaninran; Mr.S.TTyongun (Western European Studies, 2023)
This study examines the patterns of tomato and yam flow within Benue State and their respective contributions to the state's economic growth. By analyzing data on production, trade, and economic indicators. The study explores the interplay between agricultural production and economic growth. The findings reveal significant correlations between tomato and yam production volumes, as well as their impacts on key economic indicators such as GDP and employment. These insights shed light on the role of tomato and yam agricultural produce in shaping Benue State's economic landscape
Keywords: Flow patterns; Yam and Tomato; Economic growth